A Critical Period for Robust Curriculum‐Based Deep Reinforcement Learning of Sequential Action in a Robot Arm. (10th January 2022) - de Kleijn, Roy; Sen, Deniz; Kachergis, George
Abstract: Many everyday activities are sequential in nature. That is, they can be seen as a sequence of subactions and sometimes subgoals. In the motor execution of sequential action, context effects are observed in which later subactions modulate the execution of earlier subactions (e.g., reaching for an overturned mug, people will optimize their grasp to achieve a comfortable end state). A trajectory (movement) adaptation of an often‐used paradigm in the study of sequential action, the serial response time task, showed several context effects of which centering behavior is of special interest. Centering behavior refers to the tendency (or strategy) of subjects to move their arm or mouse cursor to a position equidistant to all stimuli in the absence of predictive information, thereby reducing movement time to all possible targets. In the current study, we investigated sequential action in a virtual robotic agent trained using proximal policy optimization, a state‐of‐the‐art deep reinforcement learning algorithm. The agent was trained to reach for appearing targets, similar to a serial response time task given to humans. We found that agents were more likely to develop centering behavior similar to human subjects after curricularized learning. In our curriculum, we first rewarded agents for reaching targets before introducing a penalty for energy expenditure. When the penalty was applied with no curriculum, many agents failed to learn the task due to a lack of action space exploration, resulting in high variability of agents' performance. Our findings suggest that in virtual agents, similar to infants, early energetic exploration can promote robust later learning. This may have the same effect as infants' curiosity‐based learning by which they shape their own curriculum. However, introducing new goals cannot wait too long, as there may be critical periods in development after which agents (as humans) cannot flexibly learn to incorporate new objectives. These lessons are making their way into machine learning and offer exciting new avenues for studying both human and machine learning of sequential action. Abstract : In a sequential reaching task, a robot arm trained using deep reinforcement learning optimizes its behavior in a similar manner to humans. This so‐called centering behavior, however, only tends to develop when learning is performed in a curriculum in which the reward function becomes increasingly complex over time. Furthermore, the onset of the curriculum seems to have a sensitive period, with too early or too late onset leading to unstable or suboptimal performance.